2015
DOI: 10.1016/j.pbi.2015.05.033
|View full text |Cite
|
Sign up to set email alerts
|

Small RNAs — the secret agents in the plant–pathogen interactions

Abstract: Eukaryotic regulatory small RNAs (sRNAs) that induce RNA interference (RNAi) are involved in a plethora of biological processes, including host immunity and pathogen virulence. In plants, diverse classes of sRNAs contribute to the regulation of host innate immunity. These immune-regulatory sRNAs operate through distinct RNAi pathways that trigger transcriptional or post-transcriptional gene silencing. Similarly, many pathogen-derived sRNAs also regulate pathogen virulence. Remarkably, the influence of regulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
106
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(108 citation statements)
references
References 87 publications
0
106
0
2
Order By: Relevance
“…During this process, differential expression of endogenous sRNAs accompanies defense responses to pathogen attack (Katiyar‐Agarwal & Jin, ). Studies of sRNA biogenesis and sRNA functioning genes have shown that impairing these genes reduces the defense against certain pathogens (Weiberg & Jin, ). We show here the A. tauschii AGO4a antibody specifically pulled down 24‐nt siRNAs that began with the base adenine, a typical characteristic of AGO4a proteins, as observed in Arabidopsis (Mi et al ., ) and rice (Wu et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During this process, differential expression of endogenous sRNAs accompanies defense responses to pathogen attack (Katiyar‐Agarwal & Jin, ). Studies of sRNA biogenesis and sRNA functioning genes have shown that impairing these genes reduces the defense against certain pathogens (Weiberg & Jin, ). We show here the A. tauschii AGO4a antibody specifically pulled down 24‐nt siRNAs that began with the base adenine, a typical characteristic of AGO4a proteins, as observed in Arabidopsis (Mi et al ., ) and rice (Wu et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggest that reduced DNA methylation promotes host defense responses against pathogen infection (Yu et al ., ). Among the key components of the RdDM pathway, AGO4a is required for resistance to P. syringae in Arabidopsis (Agorio & Vera, ); small RNAs (sRNAs) also play a role in plant immunity in this system (Weiberg & Jin, ). However, little information is known about DNA methylation dynamics in crops such as wheat, one of the most important staple foods worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…One such essential antiviral response is RNA silencing (4-6), a cellular mechanism conserved from lower eukaryotes to mammals to regulate endogenous gene expression at the transcriptional and posttranscriptional levels (7,8). To activate antiviral RNA silencing, the viral double-stranded RNAs (dsRNAs), which may originate during viral replication, as a result of internal pairing of viral RNA molecules, or through de novo synthesis by the host RNA-dependent RNA polymerase 6 (RDR6)/ suppressor of gene silencing 3 (SGS3) complex using viral genomic fragments as the template, are processed by Dicer-like (DCL) proteins into small 20-to 24-nucleotide (nt) RNA duplexes termed virus-derived short interfering RNAs (vsiRNAs).…”
mentioning
confidence: 99%
“…The impact of sRNA on the ecological interactions between parasites and their hosts is already well appreciated (reviewed in 156 ). The possibility of cross-kingdom regulation of gene expression via ingested sRNAs could also be of particular ecological interest.…”
Section: Discussionmentioning
confidence: 99%